2000
DOI: 10.1063/1.1321768
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the A2Πu–X2Πg band system of C7−

Abstract: The A 2 ⌸ u -X 2 ⌸ g electronic system of gaseous C 7Ϫ is examined experimentally in the light of theoretical predictions. Ab initio calculations at the RHF, RCCSD͑T͒ and MRCI levels using the aug-cc-pVQZ basis set indicate that the transition is accompanied by a small elongation in the molecule and a significant reduction in the spin-orbit coupling constant. On the basis of these predictions the band profiles of the 0 0 0 , 1 0 1 , 2 0 1 and 3 0 1 transitions were recorded using photodetachment spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…− and C 9 − anions have been found to have openshell 2 Π g and 2 Π u ground states, respectively, from investigations using rare gas matrices, 18,[37][38][39] resonance enhanced multiphoton electron detachment, [40][41][42] and electronic structure calculations. [43][44][45] Anion photoelectron spectroscopy (PES) is a powerful technique for interrogating the vibronic structure of sizeselected neutral clusters via photodetachment of the corresponding anion.…”
Section: Introductionmentioning
confidence: 99%
“…− and C 9 − anions have been found to have openshell 2 Π g and 2 Π u ground states, respectively, from investigations using rare gas matrices, 18,[37][38][39] resonance enhanced multiphoton electron detachment, [40][41][42] and electronic structure calculations. [43][44][45] Anion photoelectron spectroscopy (PES) is a powerful technique for interrogating the vibronic structure of sizeselected neutral clusters via photodetachment of the corresponding anion.…”
Section: Introductionmentioning
confidence: 99%
“…The high electron affinity and density of vibrational states of C 7 permits rapid radiative electron attachment such that anion formation has been calculated to occur every time an electron collides with C 7 (Terzieva & Herbst 2000). However, the early promise of C − 7 as a DIB carrier was quashed when high resolution observational and laboratory spectroscopy by Galazutdinov et al (1999), Sarre & Kendall (2000), Lakin et al (2000) and McCall et al (2001) identified that the match between the DIBs and the wavelengths, strengths and profiles of the C − 7 optical absorption bands was too poor to constitute an assignment.…”
Section: Previous Studiesmentioning
confidence: 99%
“…On the other hand, recent detailed analyses of DIB profiles have suggested that several of the stronger DIBs may be due to small molecules (≤ 7 heavy atoms) (Oka et al 2013;Huang & Oka 2015). While a number of such small molecules have been considered over the years, most detailed comparisons between laboratory and astronomical spectra have not yielded adequate matches (e.g., Tulej et al 1998;Motylewski et al 2000;Lakin et al 2000;McCall et al 2001;Guthe et al 2001;Salama et al 2011). Some five near-IR DIBs were recently attributed to the fullerene cation C 60 + Walker et al 2015; though see Galazutdinov et al 2017).…”
Section: Introductionmentioning
confidence: 99%